Praktek Gadai Sawah di Kabupaten Bekasi Dalam Perspektif Ekonomi Islam - MH Ainulyaqin; Saiban, Kasuwi; Munir, Misbahul (DPPM Universitas Pelita Bangsa, 2023)
The purpose of this research is to find out the views of the four schools of thought on the implementation of the field pawn system. The study was conducted in Bekasi. The research approach used is qualitative. The results of the study revealed that in terms of the ijab kobul, the implementation of the pawn was in accordance with the provisions of Islamic law even though the ijab kobul was carried out orally in the language of the local community. Meanwhile, regarding other matters regarding rahin and murtahin are also valid in accordance with the provisions of Islamic law because each party is a person who has reached puberty, is reasonable and understands the law. Marhun is also legal according to Islamic law because the rice fields are legal goods to be pawned. With the full use of paddy fields by the recipient of the pawn, this is actually not justified and illegal according to the provisions of Islamic law because there is still an element of taking opportunities in narrowness and unfairness to rahin and of course this is very contrary to the principle of muamalah.